Mathematical Approaches of Creating to Educational Content Formation in the Professional System Computer Training of Blind People - TULASHVILI, Iurii (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Paper presents relevant areas for further development of outlined problem are the development of methods for logical structuring, production models and semantic networks to simplify and optimize the procedures for transferring of educational information, improving educational and developmental process.